Impact of packet size and node mobility pause time on average end to end delay and Jitter in MANET's - Hakak, Saqib Iqbal; Anwar, Farhat; Abdul Latif, Suhaimi; Gilkar, Gulshan; Alam, Mohammed Khorshed (The Institute of Electrical and Electronics Engineers, Inc., 2014)
Mobile ad-hoc network (MANET) is a self-configuring infrastructure less network of mobile devices connected by Wireless and each node or mobile device is independent to move in any desired direction and thus link goes on changing from one node to another. In MANET's, routing is considered as one of the most difficult and challenging task and due to that reason, most of the studies have focused on comparing protocols with each other under varying network conditions. But to the best of our knowledge no one has studied effect of different factors on network performance indicators like throughput, Jitter and so on, as how much influence a particular factor or group of factors is having on network performance indicators itself. Thus, in this paper effect of three key factors i.e. Routing protocol, packet size and Node Mobility Pause time is evaluated on the key network performance metrics i.e. Average Delay and Average Jitter, as these parameters are crucial for network performance and directly affects the buffering requirements for all video devices and downstream network. Also excess value of Delay and jitter can lead to many problems ranging from lip-synchronization problem to the loss of packets because of buffer overflow or underflow.